2020
DOI: 10.1007/s11661-020-05648-w
|View full text |Cite
|
Sign up to set email alerts
|

Size Effects of Hardness and Strain Rate Sensitivity in Amorphous Silicon Measured by Nanoindentation

Abstract: In this work, dynamic mechanical properties of amorphous silicon and scale effects were investigated by the means of nanoindentation. An amorphous silicon sample was prepared by plasma-enhanced chemical vapor deposition (PECVD). Next, two sets of the samples were investigated: as-deposited and annealed in 500°C for 1 hour. A three-sided pyramidal diamond Berkovich's indenter was used for the nanoindentation tests. In order to determine the strain rate sensitivity (SRS), indentations with different loading rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…What's more, a strong influence of cutting speed occurs on the modified workpiece, where the BDT depth rapidly decreases when the tool moves faster. It is attributed by the enhanced hardness under high strain rate, which is reported in the study of nanoindentation on amorphous silicon [13]. Therefore, appropriately reducing the cutting speed is beneficial for a better surface quality.…”
Section: Applying Niim On Germanium and Tungsten Carbidementioning
confidence: 90%
“…What's more, a strong influence of cutting speed occurs on the modified workpiece, where the BDT depth rapidly decreases when the tool moves faster. It is attributed by the enhanced hardness under high strain rate, which is reported in the study of nanoindentation on amorphous silicon [13]. Therefore, appropriately reducing the cutting speed is beneficial for a better surface quality.…”
Section: Applying Niim On Germanium and Tungsten Carbidementioning
confidence: 90%
“…During nanoindentation, the loading rate or strain rate is an important influencing factor on the mechanical properties of materials [ 31 , 32 , 33 , 34 ]. Kucheyev et al studied the deformation behavior of a c-plane (0001) ZnO single crystal by nanoindentation at the micro-scale indentation depth of about 1000 nm, and found that the elastic–plastic-deformation transition threshold depends on the loading rate, with faster loading resulting in a larger threshold [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoindentation has been widely used for characterizing the mechanical properties of micro/nano-scale materials because it is high-resolution and nondestructive [ 11 ]. Nanoindentation can be used to research the dependence on the size effect, Hall-Petch effect and strain rate dependence of micro-nano-scale thin films [ 12 , 13 ], and it can even be used in the research on viscoelastic materials [ 14 ], but the measurement of basic mechanical parameters, such as of elastic moduli and hardness, is widely used. Generally speaking, the measurement reflects the composite response of the thin film and substrate.…”
Section: Introductionmentioning
confidence: 99%